1999
DOI: 10.1557/s1092578300002325
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and Nitrogen Ambient Effects on Epitaxial Lateral Overgrowth (ELO) of GaN VIA Metalorganic Vapor-Phase Epitaxy (Movpe)

Abstract: Ambient gas effect on the epitaxial lateral overgrowth (ELO) of GaN via metalorganic vapor-phase epitaxy (MOVPE) on a MOVPE-grown GaN (0001) / sapphire (0001) substrate with a SiO 2 stripe mask has been studied by means of field-emission scanning electron microscopy (SEM) and highresolution X-ray diffraction (XRD) analysis. Different ambient gases of nitrogen, hydrogen and their mixture (mixture ratio, hydrogen : nitrogen = 1 : 1) affect the lateral overgrowth rate, the surface morphology and the crystalline t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The lateral overgrowth rates and the equilibrium facets developed in the process depend on both the crystallographic orientation of the stripe openings and the growth parameters, temperature, V/III ratio in the vapour phase, pressure, composition of the carrier gas (H 2 , N 2 ), fill factor (ratio of the stripe opening to the pattern period) [59][60][61][62][63]. It has been demonstrated that the lateral expansion is easier when the stripes are aligned along h1 1 100i GaN direction [44].…”
Section: Morphology and Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral overgrowth rates and the equilibrium facets developed in the process depend on both the crystallographic orientation of the stripe openings and the growth parameters, temperature, V/III ratio in the vapour phase, pressure, composition of the carrier gas (H 2 , N 2 ), fill factor (ratio of the stripe opening to the pattern period) [59][60][61][62][63]. It has been demonstrated that the lateral expansion is easier when the stripes are aligned along h1 1 100i GaN direction [44].…”
Section: Morphology and Defectsmentioning
confidence: 99%
“…In short, from experiments carried out on h1 1 100i stripes on MOVPE GaN, Tadatomo et al [61] and Kawaguchi et al [68][69][70] concluded that H 2 as a carrier gas produces smooth surfaces, but a low lateral growth rate. Conversely, N 2 enhances the lateral growth rate, but the surface quality is poor.…”
Section: Morphology and Defectsmentioning
confidence: 99%
“…Hiramatsu et al reported that growth pressure control has a similar effect on facet formation to growth temperature in facet-controlled ELO (FACELO) technique [19]. Hydrogen and nitrogen ambient effects on facet formation have been reported by Tadatomo et al [20]. In this paper, facet control-based three-step growth was demonstrated using a mass-production-type 10 Â 2 00 MOVPE system.…”
Section: Introductionmentioning
confidence: 55%
“…It is reported that low growth pressure has a similar effect on facet formation to high growth temperature [19]. Additionally, the carrier gas mixture ratio also affects facet formation [20]. Hence, total optimization of growth process is important including t FC , T FC , P FC and R FC .…”
Section: Resultsmentioning
confidence: 99%
“…Usui et al [2] and Nam et al [3] were the first to investigate GaN MOVPE growth by the ELO technique in 1997 and achieved low dislocation densities of the order of 10 7 cm À2 instead of 10 10 cm À2 for the best GaN/sapphire template. The control of the dislocation density in ELO samples is closely related to the initial ELO GaN structure, via several experimental parameters: the pattern orientation [3], the mask material [4], the mask fill factor [5,6], the growth temperature [7], the flow rate of gas sources [7], the ambient carrier gas [8], the impurity level [9], the template quality [10] and the reactor pressure [11]. For the HVPE process, the influence of the carrier-gas composition [12,13], the growth temperature [12] and the GaN template quality [14] were studied.…”
Section: Introductionmentioning
confidence: 99%